COSMIC observations of ionospheric density profiles over Indian region: Ionospheric conditions during extremely low solar activity period - Sripathi, S. (My University, 2012)
In the present paper, for the first time, an attempt has been made to study the seasonal, altitudinal, diurnal and latitudinal variation of low latitude electron density obtained using COSMIC radio occultation (RO) measurements over Indian longitudes during the deep solar minimum year 2008. The seasonal variation shows enhanced electron densities at vernal and autumn equinoxes compared to winter and summer seasons. The observations also suggest a shift in the time and altitude at which the peak of the electron density occurs in different seasons. An important finding is that there exists an equinoctial asymmetry in the electron density with respect to altitude and latitude, where the electron density is higher at vernal equinox compared to autumn equinox. The latitudinal and seasonal variation of peak electron density (NmF2) during 10:00-14:00 hrs LT indicate enhanced equatorial ionization anomaly (EIA) on either side of the magnetic equator at both vernal and autumn equinoxes compared to the other seasons. Seasonal variation of equatorial electrojet (EEJ) strength obtained from geomagnetic H-field variations also shows strong EEJ at vernal and autumn equinoxes indicating that EEJ strength indeed partly controls the EIA development. Further, the results indicate that NmF2 over the northern EIA crest region is correlated well with solar flux.
Keywords: Electron density; Equatorial ionization anomaly (EIA); Equatorial electrojet (EEJ) strength; Ionospheric density; Equinoctial asymmetry